The education of financial culture in children of merchant families in Tacna - Ticona Cohaíla, Juana Guisella (2023)
Tacna is a Peruvian border city whose main economic activity is family business; therefore, the development of the financial culture plays an important role in the formation of the next generations that will lead the family businesses. From this, an investigation was carried out to know the characteristics of the financial education of children whose direct family environment is dedicated to commerce, both formal and informal. For this, a mixed methodology was used based on surveys and interviews applied to students in the last grade of the primary education level of three educational institutions. The capacities of the 19th competency of the Peruvian Regular Basic Education were used as observation criteria. From this, it was found that these students have developed the financial culture; however, the school has little participation in the acquisition of such knowledge. Instead, it is the family and the children's direct link to the family business that influences their financial culture. The results show the importance of the family as the main educational agent and generator of a habitus. Likewise, the need for an educational system contextualized to the social and economic reality of the city is emphasized.